2004
DOI: 10.1002/jbt.20003
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorous and organochlorine pesticides affect human placental phosphoinositides metabolism and PI‐4 kinase activity

Abstract: The objective of this work was to describe the effect of organophosphorous and organochlorine pesticides on phosphoinositides metabolism in human placenta. Pesticides concentration (10 microM) was used for in vitro incubations of cell-free homogenates labelled with (32)P orthophosphate. Heptachlor (HC) and dichloro-diphenyl-trichloroethane (o-p' DDT) increased phosphatidyl-inositol, phosphatidylinositolphosphate, and phosphatidyl-inositolbiphosphate phosphorylation while azinphosmethyl (AM) increased phosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…In accordance with these results, in vitro studies also demonstrated that different OCs (endosulfan, DDE, and dieldrin) can rapidly activate ERKs in the pituitary tumor cell line GH 3 /B6/F10, with distinctly different activation patterns [29]. Also, we have demonstrated that human placenta presents differential effects of 10 μM HC and o-p DDT on nuclear PI-4 kinase activity [30].…”
Section: Discussionsupporting
confidence: 68%
“…In accordance with these results, in vitro studies also demonstrated that different OCs (endosulfan, DDE, and dieldrin) can rapidly activate ERKs in the pituitary tumor cell line GH 3 /B6/F10, with distinctly different activation patterns [29]. Also, we have demonstrated that human placenta presents differential effects of 10 μM HC and o-p DDT on nuclear PI-4 kinase activity [30].…”
Section: Discussionsupporting
confidence: 68%
“…However, both types of pesticides affected the post-membrane supernatant of PI 4-kinase, a key enzyme in PI metabolic pathway. A biphasic effect on membrane and nuclear PI4-kinase activity was seen with heptachlor (OC), with the strongest effect being found with o-p'-DDT on nuclear PI4-kinase activity, while substantial changes were also observed in membrane fractions (Souza et al, 2004).…”
Section: Targetmentioning
confidence: 98%
“…Abdel-Rahman and colleagues (2002) further concluded that though the placenta presents a barrier of protection against CPF; at high doses, CPF and its metabolites can cross the placenta and enter into the fetus despite extensive maternal hepatic metabolism, as well as, distribute to all fetal tissues and plasma with elimination occurring at a slow rate. In addition, Souza et al (2004) demonstrated that CPF alters the enzymatic activity of placental PI4-kin ase and phosphatidylinositol handling suggesting that CPF may have membrane disrupting properties. Given that exposure to xenobiotics can alter the function and viability of placenta cells, thereby ostensibly, altering the growth and development of the fetus, we examined whether chlorpyrifos and its metabolites are toxic to placental cells.…”
Section: Introductionmentioning
confidence: 99%